Origin of the Phacoid Structures within the Chia Gara Formation, Kurdistan Region, Iraq - Ahmed, Sirwan H.; Mohialdeen, Ibrahim M. J.; Muhammed, Hemin F. (Sulaimani Journal for Pure and Applied Sciences, 2020)
Special structural shapes exhibit occurrence in the sequence of Chia Gara Formation in the northwestern part of the Zagros belt in Kurdistan region-Iraq. These structures name as Phacoids that have spherical to semi-spherical shape. Constructing concentric zonal features in the carbonate/shale of Chia Gara Formation. These structures are characterized by the presence of ball-like bodies within the host rocks. The diameter of phacoids ranged from 20cm to about 120cm. They are harder than the host rock. Seven outcrop sections, of Chia Gara Formation are reviewed and two of them studied in detail to determining the origin and process of their formation. The phacoids can be conceder as sedimentary key marker to recognize the Chia Gara Formation in the outcrops. Petrographically, the phacoids are mostly organic matter–rich bioclastic lime wackestone. The bitumens are present in sub-parallel lines in a calcareous groundmass. However, the host rock is generally composed of calcareous shale rich in organic matter but barren of fossils. The carbonate phacoids were forming in a competent/incompetent sequence. The mechanism of creating these carbonate phacoids structures are related to the compression stress and diagenesis processes on the carbonate/shale successions. Some phacoids directly formed from the carbonate strata after separated and rolled due to continue compression shear stress that in the final stage form the carbonate phacoid with the aids of diagenesis.
Keywords: Chia Gara Formation; Phacoid structures; Jurassic; Kurdistan